Implementasi Program Corporate Social Responsibility (CSR) Perseroan Terbatas Pertamina dalam Pengembangan UMKMs - Firmansyah, Shofwan Muhammad; Hardjati, Susi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
Indonesia is a country that is rich in natural resources, such as abundant oil content so that if it is managed properly, Indonesia will become a very prosperous country. PT. Pertamina (Persero) RU-VI Balongan is a refinery company that processes state oil and natural gas to provide and serve the needs of oil and non-oil fuels for the wider community. As one of the companies that fall into the category of State-Owned Enterprises (BUMN), PT Pertamina is a company that has social responsibility as stipulated in the Law of the Republic of Indonesia No.40 of 2007. So this study aims to find out how the implementation of the CSR Program in the development of UMKM in Balongan District by PT. Pertamina RU VI Balongan. The research method used in this study is a qualitative research method with data collection techniques in the form of interviews and observations based on the Policy Implementation Theory of David C Korton with program indicators, implementing organizations, and target groups and . The research location is in Balongan District, Indramayu Regency. The research results show that the implementation of the CSR program by PT. Pertamina Persero has had an important influence on the development of MSMEs in Balongan District, especially for MSMEs with business actors, namely former female workers (ex-tkw) who are members of the creative air group.